Demographic variables and their impact on the level of job performance of employees of the Ministry of Labor in the Sultanate of Oman - Al-Hudaifi, Mohammed Salim; El-Amili, Omar (Journal of Economic, Administrative and Legal Sciences, 2022)
The current study aimed to identify the reality of job performance and the impact of demographic variables on the level of job performance among employees of the Ministry of Labor in the Sultanate of Oman. The study has followed the descriptive analytical approach, and the questionnaire was selected as an essential means of data collection. The (337) questionnaires were distributed to the study sample from various administrative divisions of the Ministry, and the data was analyzed by the Statistical Package of Social sciences (SPSS). The results of the study revealed that the level of job performance among employees of the Ministry of Labor in Oman is very high. The results also showed that there are no statistically significant differences between the following variables (age, scientific qualification, career level, and number of years of service) and level of job performance, except the gender variable, where statistical differences were in favour of the male sample.